NATURAL KOSMETIK BERBAHAN EKSTRAK CAIR PROPOLIS SEBAGAI AGEN TABIR SURYA DALAM SEDIAAN LOTION DENGAN VARIASI ASAM STEARAT SEBAGAI EMULAGTOR - Sholichah Rohmani; Wahyu Alfhaza Ibnu Adhe; Meissy Rochmawati; Anindya Hayu Maheswari; Desi Syiamsih; Nenda Devi Nurlita; Rifanie Putri Az Zahra; Salma Ratnadila Irwanda; Tiara Amalia Firdaus; Kartini Putri Maharani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Sunscreen is a preparation used on the surface of the skin that works to absorb, scatter or reflectrays ultraviolet. One of the compounds that have benefits as a sunscreen is propolis. Propolis has antioxidant activity and its components can be used as a sunscreen formulation. The flavonoids contained in propolis have potential as sunscreen because of the presence of a chromophore group (conjugated double bond) which can absorb both UV B and UV A rays. To make a good preparation, a good formula is needed, one of the components in making lotions is acid. stearicate used as emulgator. This study aims to formulate a lotion with variations of stearic acid which functions as anas emulgator well as to test the physical and chemical properties of thepreparations lotion. The lotion is made in three variations of the composition of stearic acid, namely 2.5%: 5%; 7.5%. The lotion obtained was evaluated for the physical and chemical properties of thepreparation lotion including organoleptic test, homogeneity, emulsion type, pH, spreadability, adhesion and viscosity as well asmeasurement of the SPF value in vitro. The results of the analysis showed that variations in the concentration of stearic acid had a significant effect on the physical properties of the lotion including the results of pH, spreadability, adhesion, and viscosity. Stearic acid the higher the viscosity, consistency, and increased adhesion but the spreadability decreases. The SPF test results on theformula were lotion 6.13 (F1), 6.11 (F2), and 6.05 (F3) and the SPF value decreased after thetest freeze thaw.